A Subtitling Analysis Of Simple Sentence In Begin Again By Dhikancut - Setiawan, Wahyu, Dr. Dwi Harjanti M. Hum (2016)
This research focuses on the subtitling analysis of simple sentence in Begin Again by Dhikancut using Gottlieb's theory about subtitling strategy and Nababan's theory about subtitling readabilty. The objectives of this research are (1) to identify the subtitling strategies of simple sentence found in Begin Again (2013) movie and (2) to describe the subtitling readability of simple sentence found in Begin Again (2013) movie. The type of this research is descriptive qualitative. The object of this research is the Begin Again (2013) movie script. The researcher uses documentation and interviewing technique to collect the data. The researcher uses triangulation to prove the validity of the research where the data sources are from movie and informant. The researcher obtains 1612 data which use subtitling strategies in Begin Again (2013) movie script. There are Expansion 0,68%, Paraphrase 14,27%, Transfer 70,91%, Imitation 2,85%, Condensation 1,55%, Deletion 9,62%, and Resignation 0,12%. The most subtitling strategy used is Transfer, because the subtitler translates the source text completely and accurately. From 1612 data, there are 2 data of Resignation strategy and it is not able to be analyzed. There are 1601 data has 3 score of readability level or 99,44% and 9 data has 2 score of readability level or 0,56%. It shows that the most readability level in this research is high. It can be concluded that Begin Again (2013) movie subtitle is readable.